2018
DOI: 10.1097/prs.0000000000004600
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Late Posttraumatic Enophthalmos Correction

Abstract: This is the largest case series evaluating functional outcomes of patients undergoing post-traumatic delayed enophthalmos repair. A multidisciplinary care approach resulted in improved globe position, eye movement, and improvement of diplopia. Further studies with larger sample sizes are needed to better understand and treat this important and challenging problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, corrective surgery is necessary because enophthalmos often causes malformations, and if untreated, it may cause functional problems such as binocular diplopia. The correction of enophthalmos aims to restore the volume of the orbit and the position of its contents to improve both function and shape [1]. Various treatment methods for ocular depression have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, corrective surgery is necessary because enophthalmos often causes malformations, and if untreated, it may cause functional problems such as binocular diplopia. The correction of enophthalmos aims to restore the volume of the orbit and the position of its contents to improve both function and shape [1]. Various treatment methods for ocular depression have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Enophthalmos is defined as posterior displacement of the eyeball due to volume changes in the bony orbit. It occurs when the balance between the bony orbit and the orbital contents (i.e., the globe, orbital fat, and muscular and ligamentous support) is disrupted [1]. Two to three millimeters of enophthalmos is clinically detectable, and more than 5 mm is disfiguring [2].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of functional outcomes following late posttraumatic enophthalmos correction, the largest case series to date was published in 2018. 93 This study assessed 41 patients and found that a substantial functional improvement (defined as a decrease of greater or equal to one grade of diplopia) was achieved in 65.9 percent of patients after all surgical interventions. Those with residual diplopia after enophthalmos surgery were managed with secondary strabismus surgery or prism glasses.…”
Section: Surgerymentioning
confidence: 97%
“…Complications that can occur following enophthalmos repair are similar to those following primary repair. 61,93,95,96 Risks include lid malposition such as entropion, ectropion, and vertical lid shortening, and asymmetry in palpebral fissure width or inclination. Visual disturbances, ranging from corneal abrasion to retrobulbar hemorrhage and possible blindness, can occur.…”
Section: Complicationsmentioning
confidence: 99%
“…Extraocular muscle entrapment and ischemic change, trapping, or prolapse of the orbital soft tissue may result in ocular motility limitations, diplopia, and visual dysfunctions. In addition, esthetically debilitating conditions, such as enophthalmos or globe displacement, may appear with large bony defects [ 3 ].…”
Section: Introductionmentioning
confidence: 99%